2014
DOI: 10.1128/jcm.01195-14
|View full text |Cite
|
Sign up to set email alerts
|

Neurotropic Astrovirus in Cattle with Nonsuppurative Encephalitis in Europe

Abstract: e Encephalitis is a frequently diagnosed condition in cattle with neurological diseases. Many affected animals present with a nonsuppurative inflammatory reaction pattern in the brain. While this pattern supports a viral etiology, the causative pathogen remains unknown in a large proportion of cases. Using viral metagenomics, we identified an astrovirus (bovine astrovirus [BoAstV]-CH13) in the brain of a cow with nonsuppurative encephalitis. Additionally, BoAstV RNA was detected with reverse transcription-PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
145
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(152 citation statements)
references
References 24 publications
4
145
1
2
Order By: Relevance
“…Phylogenetic tree analysis and pairwise amino acid identity comparison revealed that all but one of the detected Japanese BoAstVs were closely related to BoAstVs reported from other countries and shared similarities with them. No Japanese BoAstVs were related to the BoAstV strains NeuroS1 and CH13, which were previously detected in cattle suffering from neurologic disease [9,10]. Almost all BoAstVs clustered with BoAstV lineage 1, including Chinese BoAstVs, while three Japanese strains and one American strain clustered with lineage 2.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Phylogenetic tree analysis and pairwise amino acid identity comparison revealed that all but one of the detected Japanese BoAstVs were closely related to BoAstVs reported from other countries and shared similarities with them. No Japanese BoAstVs were related to the BoAstV strains NeuroS1 and CH13, which were previously detected in cattle suffering from neurologic disease [9,10]. Almost all BoAstVs clustered with BoAstV lineage 1, including Chinese BoAstVs, while three Japanese strains and one American strain clustered with lineage 2.…”
Section: Discussionmentioning
confidence: 92%
“…However, the association of BoAstVs with diarrheic disease remains unclear, because experimental infection studies have failed to produce clinical disease [8]. Recently, neurologic disease in cattle characterized by encephalomyelitis and ganglioneuritis caused by BoAstVs was reported in the USA and Europe [9,10]. A novel BoAstV, BoAstVNeuroS1, and BoAstV-CH13 were reported to be genetically related to an ovine astrovirus (OAstV) in Scotland in 1977 [11].…”
Section: Introductionmentioning
confidence: 98%
“…In minks, an astrovirus genotype is the causative agent of shaking mink syndrome, a neurological disorder of minks characterized by tremors and seizures (40,41). Bovine astroviruses have been identified as a significant cause of encephalitis in cattle, as these viruses have been detected in 34% of previously unexplained cases of encephalitis (42)(43)(44)(45)(46)(47). An additional astrovirus genotype has also been identified as a cause of encephalitis in sheep (48).…”
mentioning
confidence: 99%
“…Although there have been some reports in recent years describing the possible role of AstVs in encephalitis (Blomström et al, 2010;Bouzalas et al, 2014;Brown et al, 2015), the commonest disease associated with AstVs is gastroenteritis. This has been most thoroughly studied for human AstVs, which are distributed worldwide and are associated with up to 20 % of acute, non-bacterial gastroenteritis in children in some studies (De Benedictis et al, 2011;Gaggero et al, 1998;Guix et al, 2002;Kirkwood et al, 2005;Moser & Schultz-Cherry, 2005;Naficy et al, 2000).…”
Section: Discussionmentioning
confidence: 99%